Desigualdad de género en la televisión ecuatoriana - Zamora Rodríguez, Belia María (2023)
In the following work, inequality and how it sometimes causes situations of harassment that women have to face in the area of communication, taking as an example the case of a digital sports program. In order to obtain information that will help the research, we start with topics about gender inequality in general and with in Ecuador, until we get to explain in more detail the difficulties faced by women in the television field. To achieve a deeper analysis of the topic, interviews and focus groups were conducted with both women and men to have different opinions and points of view, and also based on their experience, to achieve a deeper understanding of this research work.